Development of a WEBGIS-Mapping Information System of Tuberculosis (MISS TB) For Plotting Tuberculosis Cases: A Case Study in Sleman District, Yogyakarta Province, Indonesia - Rohman, Hendra; Nurrochman, Alwhan (Procedia of Engineering and Life Science, 2024)
Geographic information system for health information management and public health to analyze the spatial disease distributions in surveillance has increasingly applied in the last few decades. The programming skills needed to utilize the software appropriately in contact tracing and follow up control measures for tuberculosis (TB) patients. This study aimed to develop a more user friendly application by applying XAMPP application to create WEBGIS localhost, PHP My Admin for MySQL database management, MySQL server as a database management system (DBMS), Visual Studio Code application for creating programming. The system development method uses a waterfall model. These data were collected from infectious disease prevention and control officers at the Sleman District Health Service and tuberculosis reporting programmer officers at community health centers. Data on rainfall, humidity, altitude, temperature, area, population and population density were obtained from the Central Statistics Agency of Sleman Regency. Data visualization in mapping for 17 sub-districts in Sleman Regency. The geographic menu contains information on rainfall, humidity, altitude and temperature for each month in tabular form. The demographics menu contains information on the area, population and population density of each sub-district in tabular form. The distribution location input menu is used to add data on tuberculosis cases. The distribution list menu contains a table that contains a database stored from the location input. The account menu on the administrator user contains a list of accounts created or registered in system. The website-based geographic information system (GIS) application is expected to improve case data reporting, case monitoring, support data availability, and visualize the distribution of tuberculosis cases in Sleman Regency through the mapping menu. The application developed should assist health information management and public health experts to utilize medical record data and spatial data for the surveillance purposes comprehensively.